Combination of discontinuity characteristics and GIS for regional assessment of natural rock slopes in a mountainous area (NE Turkey) - Bostanci, Hasan Tahsin; Alemdag, Selcuk; Gurocak, Zulfu; Gokceoglu, Candan (Elsevier Science Bv, 2018)
Geographical Information Systems (GIS) have a very large spectrum of users. As in many engineering applications, GIS are frequently used in geotechnical projects, especially in producing various thematic and zoning maps such as various susceptibility and hazard maps. Instability maps for large areas with similar characteristic can be produced in a practical way by evaluating the results obtained by the data collected from field and laboratory studies. In order to introduce a methodology for producing rock slope instability maps for a large area, discontinuity controlled slope failures in the Kose Granitoid Complex (NE Turkey) were selected. To determine the types of failure such as planar, wedge, and toppling, and possible instable slope orientations kinematic analyses were carried out in the limited areas. The relationships between orientations of natural slopes and discontinuities obtained from kinematic analyses were evaluated with GIS software. Finally, discontinuity controlled instability maps were produced for the study area. Resulting maps show that the most common type of failure is wedge type. Additionally, the distributions of unstable areas along road networks were determined. Various land use types such as agriculture, grassland, settlement, and forest were also classified in order to predict the possible effects of slope instabilities. The methodology introduced in this study indicates highly promising results for the assessment of rock slope instability in large areas.
Keywords: GIS; Instability map; Kinematic analysis; Rock slope stability